Cryptography algorithms for enhancing security in IoT based Mafly- MPPT system under partial shading conditions - Pragathi, B.; Rao, B. K. Karunakar; Rao, L. Shanmukha; Kumar, Y. Anil; Pandraju, Thandava Krishna Sai; Chinta, Anil Kumar (Journal of discrete mathematical sciences & cryptography, 2024)
In the realm of renewable energy, the integration of Internet of Things (IoT) technologies with Maximum Power Point Tracking (MPPT) systems has gained significant attention for optimizing photovoltaic (PV) performance, especially under partial shading conditions. However, the increased interconnectivity also introduces substantial cybersecurity risks. This paper presents a comprehensive study on the implementation of advanced cryptography algorithms to enhance the security framework of IoT-enabled Mafly-MPPT systems. By safeguarding data integrity and ensuring secure communication between system components, the proposed cryptographic solutions mitigate potential threats and vulnerabilities. Through extensive simulation and analysis, the study demonstrates the effectiveness of the algorithms in maintaining system efficiency and resilience in dynamic environmental conditions, highlighting the critical role of robust security measures in the future of renewable energy systems.